Monitoring the neural activity associated with praying in Sahaja Yoga meditation - Oscar Perez-Diaz; Alfonso Barrós-Loscertales; Uffe Schjoedt; José L. González-Mora; Katya Rubia; José Suero; Sergio Elías Hernández (BMC Neuroscience)
Abstract Background Sahaja Yoga Meditation draws on many religious traditions and uses a variety of techniques including Christian prayer to reach a state known as thoughtless awareness, or mental silence. While there are many studies on the neural correlates of meditation, few studies have focused on the neural correlates of praying. Thus, the aim of our research was to study the neural activity associated with the prayer practices in Sahaja Yoga Mediation, which have not been studied before, to explore effects beyond repetitive speech or “mantra effects”. Sixteen experienced Sahaja Yoga Meditation practitioners were scanned using task based functional Magnetic Resonance Imaging while performing formalised and improvised forms of praying and their equivalent secular tasks. Results Our results showed the deactivation of bilateral thalamus during both prayers compared to secular conditions and the activation in the medial prefrontal cortex that was reduced by religious and formalised secular speech conditions but increased during improvised secular speech; similarly, frontal regions were deactivated when comparing prayers to their secular equivalents. Discussion These results seem to depict two important factors related with praying in Sahaja Yoga Meditation merging inner concentration and social cognition. First, the perception of the surroundings mediated by the thalamus may be decreased during these prayers probably due to the establishment of inner concentration and, second, frontal deactivation effects could be related to reduced social judgement and ‘mentalizing’, particularly in the medial prefrontal cortex. Our findings suggest that praying by Sahaja Yoga Meditation practitioners is neurophenomenologically different from the social cognitive attempt of praying within Christian praying practices.